Understanding Quality Control of Hard Metals in Industry ‐ A Quantum Mechanics Approach. Issue 6 (18th April 2019) - Lattemann, Martina; Xie, Ruiwen; Lizárraga, Raquel; Vitos, Levente; Holmström, Erik
Abstract: For many decades, the magnetic saturation of, for example, hard metals (HM) such as WC‐Co‐based cemented carbides, has been used as process and quality control in industry to ensure consistency of product properties. In an urge to replace cobalt as a binder phase, a demand on understanding the magnetic response as a function of composition on the atomic scale is growing. In this paper, a theoretical description of the measured weight‐specific magnetic saturation of hard metals as a function of the tungsten weight fraction present in the cobalt binder phase, based on first‐principle calculations, is established for standard WC‐Co. The predicted magnetic saturation agrees well with the experimental one. Furthermore, it is proposed that the theoretical description can be extended to alternative and more complex binder phases which allows to transfer the production control to those hard metals. Abstract : Density functional theory calculations ensure quality control for alternative binders in the hard metal industry. In an urge to replace cobalt as binder, a demand on transferring magnetic property measurements for quality control to new binder phases arises. The proposed theoretical description of the magnetic response of Co‐bonded hard metals is extended to alternative and complex binder phases.